THE INFLUENCE OF EDUCATION AND TRAINING ON EMPLOYEE PERFORMANCE AT THE OFFICE OF REGIONAL DEVELOPMENT PLANNING AGENCY, SIDRAP DISTRICT (BAPPEDA) - Ulyana Muslimin; Pandi Putra (Universitas 17 Agustus 1945 Surabaya, 2023)
The Influence of Education and Training Against Employee Performance at the District Regional Development Planning Agency Office Sidrap (BAPPEDA). Study This aim For see how much big the influence of education and training programs for performance employee Good in a manner Partial nor in a manner simultaneous , and for measure enhancement performance employee after participate in education and training programs . The analytical method used : Validity Test , Reliability Test , Analysis Statistics Descriptive , Analysis Multiple Linear Regression and t-test ( parsil ), F-test ( simultaneous ). R2-test ( coefficient determination ). Research results This is method qualitative and quantitative , and distributed 30 questionnaires to respondents and process data for show that education and training influential in a manner partial and simultaneous . We got take conclusion that research results show that Education (X1) has an effect in a manner Partial with t count value 2.752 > t table 2.051, value significant 0.010 <0.05, training (X2) has an effect in a manner Partial with t count value 3.032 > 2.051 value significant 0.005 <0.05 on the performance of employees of the Regency Regional Development Planning Agency Sidrap (BAPPEDA).